Cognitive styles in the context of modern psychology toward an integrated framework of cognitive style. [article]. - Kozhevnikov, Maria
The goals of this article are to elucidate trends and perspectives in the field of cognitive style research and to propose an integrated framework to guide future research. This is accomplished by means of a comprehensive literature review of the major advances and the theoretical and experimental problems that have accumulated over the years and by a discussion of the promising theoretical models that can be further developed, in part, with modern neuroscience techniques and with research from different psychological fields. On the basis of the research reviewed in this article, the author suggests that cognitive styles represent heuristics that individuals use to process information about their environment. These heuristics can be identified at multiple levels of information processing, from perceptual to metacognitive, and they can be grouped according to the type of regulatory function they exert on processes ranging from automatic data encoding to conscious executive allocation of cognitive resources.-- (from the author)